2018
DOI: 10.1002/macp.201800177
|View full text |Cite
|
Sign up to set email alerts
|

Sugar‐Derived Poly(β‐thioester)s as a Biomedical Scaffold

Abstract: The monomer isosorbide diacrylate (iSDA) and commercially available dithiols allowed access to a range of biosourced, degradable polymers. Altering the dithiol identity significantly affected the glass transition Tgs of the polymer products; however, polymers did not exhibit Tgs above room temperature. Incorporating the comonomer N,N′‐methylene bisacrylamide provided mechanical reinforcement through hydrogen bonding, resulting in soft, pliable materials. Differential scannin calorimetry (DSC) and variable‐temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…All NMR experiments were performed at 298 K on a Bruker DPX-400 NMR instrument equipped operating at 400 MHz for 1 H (100.57 MHz for 13 C). 1 H NMR spectra are referenced to residual proton solvent (δ 7.26 for CDCl 3 δ 2.50 for DMSO) and 13 C NMR spectra are referenced to the solvent signal (δ 77.2 for CDCl 3 δ 39.52 for DMSO). The resonance multiplicities are described as s (singlet), d (doublet), t (triplet), q (quartet) or m (multiplet).…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…All NMR experiments were performed at 298 K on a Bruker DPX-400 NMR instrument equipped operating at 400 MHz for 1 H (100.57 MHz for 13 C). 1 H NMR spectra are referenced to residual proton solvent (δ 7.26 for CDCl 3 δ 2.50 for DMSO) and 13 C NMR spectra are referenced to the solvent signal (δ 77.2 for CDCl 3 δ 39.52 for DMSO). The resonance multiplicities are described as s (singlet), d (doublet), t (triplet), q (quartet) or m (multiplet).…”
Section: Measurementsmentioning
confidence: 99%
“…[7][8][9] More recently bio-based bicyclic diols have gained significant attention in thermoplastic polymers. [10][11][12][13] Wang and co-workers reported that incorporation of isosorbide, a simple isohexide unit, in polyesters led to a higher T g and lower polymer crystallinity. 14 Increasing isosorbide content also correlated with the speed at which hydrolytic degradation occurred.…”
Section: Introductionmentioning
confidence: 99%
“…By chemical polycondensation, the reaction temperature is quite high and a toxic catalyst is used. Base‐catalyzed thiol–ene step‐growth polymerization is another main synthesis strategy . In this approach, dithiol monomers and di(meth)acrylate monomers are typically copolymerized in the presence of nucleophilic bases as catalyst under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Junkers and co‐workers reported a series of linear biodegradable poly( β ‐thioether ester)s obtained by hexylamine‐catalyzed thiol–ene Michael additions at room temperature. Long and co‐workers prepared a range of sugar‐derived poly( β ‐thioether ester)s by a Michael‐type polyaddition using DBU as the catalyst. Several architectures of poly( β ‐thioether ester)s, such as linear, hyperbranched and network polymers, have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation